Establishment of an orthotopic model of endometrial cancer - E. M. Frantsiyants; A. I. Shikhlyarova; I. V. Kaplieva; V. A. Bandovkina; Yu. A. Pogorelova; I. V. Neskubina; L. K. Trepitaki; E. I. Surikova; T. I. Moiseenko; N. D. Cheryarina; V. M. Kotieva; A. A. Vereskunova; et al. (Сибирский онкологический журнал, 2025)
The purpose of this study was to establish a model of uterine carcinoma in female laboratory rats by transplanting Guerin carcinoma directly into the uterine horn. Material and Methods. Fifteen nonlinear white laboratory rats weighing 250 ± 25 g served as the subjects of surgical intervention. all operative interventions were performed under xylazine-zoletil anesthesia. Female white laboratory rats were laparotomized under aseptic conditions using anesthesia. the incision length was 2 cm, and a tumor suspension containing 2.5-3.5×106 cells was injected into the lumen of the right uterine horn using an intravenous catheter with a 22G injection port (0.9 × 25 mm). tumor cells were counted using the ADAMIILS cell analyzer (Nano Entek, Korea). the tumor progression was monitored for 21 days. after euthanizing the animals under ether anesthesia, median longitudinal histological sections, 5–7 μm thick, were made from the tumor node and stained with hematoxylin-eosin and Van-Gizon using standard techniques. Results. Following the transplantation of Guerin’s carcinoma cell suspension, a tumor node of approximately 25 mm in diameter was identified macroscopically in the region of the inferior aspect of the right uterine horn. additionally, the presence of haemorrhagic effusion was documented in the abdominal cavity and tumor screenings. at light microscopy, areas of neutrophilic infiltration, significant narrowing of the lumen of the uterine horn with signs of involution, and prismatic epithelium of papillary structures were observed. the tumor cell features characteristic of Guerin’s carcinoma are preserved in the tumor node induced in the uterus, with a cytoplasmic-nuclear ratio that remains close to 1:1. the shapes of the nuclei vary, but the irregular ovoid shape remains dominant, and pathological mitotic figures are observed. the tumor stroma includes cytoplasmic branched connections connecting the tumor conglomeration. Conclusion. therefore, according to the morphological description, the presented experimental model demonstrates the possibility of intrauterine growth of Guerin’s carcinoma in animals and is most similar to the localization of the tumor focus in patients with gynecological cancer.